Rancang Bangun Perangkat Wearable Pemantau Kondisi Kesehatan di Masa Pandemi Covid-19 - Endang Sri Rahayu; Listanto Listanto; Reza Diharja (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Wearable device is a device that is worn on the body to measure the clinical parameters of the body. The purpose of using this tool is to determine the value of each parameter being measured. In this research on the design of wearable to monitor health conditions during the Covid-19 pandemic, wearable made to measure body temperature, oxygen saturation (SpO2) which is a clinical parameter of the body during the Covid-19 pandemic. In addition to helping prevent the transmission of the Covid-19 virus, this tool also realizes physical distancing automatically. This study describes the manufacture of technological tools that are appropriate and useful for the community, as a solution to the problem pandemic Covid-19This tool can perform (1) physical distancing automatically, (2) monitor oxygen saturation (SpO2) in real time. (3) monitored body temperature in real time, and equipped with an Android application for monitoring. The variables studied in this study were the manufacture of tools equipped with Bluetooth Low Energy (BLE) technology, besides the microcontroller and an android application based on the Dart programming language with the Software Development Kit Flutter from the results of observations and analysis, it is known that BLE technology is efficient for use for Internet of Things, and short-range communication. BLE can realize distance measurements to provide physical distancing automatically by using Received Signal Strength Indication (RSSI), ranging from 0cm to100 cm. The results of measuring SpO2 and body temperature on wearable monitor health conditions during the Covid-19 pandemic using the MAX30102 sensor can work well. The results of the SpO2 measurement get a standard deviation value of 0.96%, while the results of body temperature measurements get a standard deviation value of 1.64%.